PERANCANGAN DAN IMPLEMENTASI GAME SIMULASI UNTUK MENGETAHUI NEUROTISME BERDASARKAN INTERNATIONAL PERSONALITY ITEM POOL - Satria, Thomas Galih; Panggabean, Francisco Maruli; Sudarma, Hantze (Infotech: Journal of Technology Information, 2019)
The game or game is an interactive activity that can quickly provide feedback between players and the system. Players can learn through discovery, practice, and feedback rather than absorb information so that it is easier to transfer the knowledge they gain from playing experience to the real world of work. The International Personality Item Pool - Neuroticism, Extraversion & Openness (IPIP-NEO) is a personality test based on the Big Five Personality theory in which the test takes the form of a questionnaire. The purpose of this research is to design an alternative media in using IPIP-NEO especially the neuroticism part in a simulation game. The problem raised was that IPIP-NEO's personality test was a questionnaire that did not provide a situation description of the questions asked to respondents. Based on existing problems, data collection in the form of literature studies, questionnaires, and interviews with experts, can be made the need for making games. The game results are then evaluated using a questionnaire aimed at samples from Non Probability Purposive Sampling. Based on the evaluation results from the questionnaire, NeuroTest gets 76% of users who feel that the results of the game provide the right depiction for themselves.